2015
DOI: 10.1038/emm.2015.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane on tight junction protein expression and PKC-α translocation after pulmonary ischemia–reperfusion injury

Abstract: Pulmonary dysfunction caused by ischemia-reperfusion injury is the leading cause of mortality in lung transplantation. We aimed to investigate the effects of sevoflurane pretreatment on lung permeability, tight junction protein occludin and zona occludens 1 (ZO-1) expression, and translocation of protein kinase C (PKC)-α after ischemia–reperfusion. A lung ischemia-reperfusion injury model was established in 96 male Wistar rats following the modified Eppinger method. The rats were divided into four groups with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…PKCα is a typical PKC isoform primarily expressed in vascular endothelial cells and the central nervous system ( 41 ). PKCα increases and decreases TJ permeability ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…PKCα is a typical PKC isoform primarily expressed in vascular endothelial cells and the central nervous system ( 41 ). PKCα increases and decreases TJ permeability ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…α1-antitrypsin [38*], anti-cytokine [11], or anti-HMGB1 [39] agents); 3) ventilation with gaseous molecules (e.g. carbon monoxide [40]) or inhaled anesthetic sevoflurane [41] that display anti-inflammatory properties; 4) growth factors (e.g. keratinocyte growth factor-2 [42]); 5) dietary supplements such as creatine [43]; and 6) cell-based therapies such as application of mesenchymal stem cells [44,45].…”
Section: Strategies To Limit Ir Injurymentioning
confidence: 99%
“…Once activated, PKC can transmit signals to the nucleus via different signal transduction pathways. Acute stimulation of PKC has been reported to be associated with intracellular translocation ( 33 ). Chen et al ( 34 ) demonstrated that activation of nPKCδ increased the damage induced by ischemia and caused cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%